Topology Study of Milking Machine Based Parametric Modeling - Novi Sukma Drastiawati; Ahmad Ajib Ridlwan; Sri Handajani; Iskandar Iskandar; Muamar Zainul Arif; Wahyu Dwi Kurniawan; Agung Prijo Budijono; Bidya Nur Habib (Logistic and Operation Management Research (LOMR), 2023)
The large market for cow's milk makes the order capacity for cow's milk high and will increase the milking process. In the production process, especially the milking process, people still manually use their hands, so fatigue often occurs, especially in people with more than 2 livestock. This causes the production process to be ineffective and the production results are also limited. Creating an automatic milking machine equipped with a milk can, a vacuum tube and a hose. Besides, a topology study will also be carried out based on the model of the machine. The three-unit component will affect the performance of the Milking Machine, especially the milk collector and milk can. Their size needs to be analyzed to get the optimum one. Optimization results for the topology of the milk collector bore diameter showed that the milk flow rate in the milk collector at a bore diameter of 9mm was 6,154 ltr/min, at a bore diameter of 14 mm was 26,566 ltr/min and at a bore diameter of 19mm was 66,128 ltr/min (conditions without being connected to hose). The shape of a milk can with a reduction of 30% from the initial weight, which is 3,358 kg to 2,350 kg, is owned by a milk can with the most optimal cone-dome tube shape. The difference in weight with the tube is generally 1,008 kg. The quantity flow when installed with a 2m long hose is 6,729 ltr/min